2019
DOI: 10.1108/md-01-2017-0090
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the social innovation process in a large market based social enterprise

Abstract: PurposeThe purpose of this paper is to investigate the organising of social innovation in a large market-based social enterprises from the perspective of dynamic capabilities and social transformation.Design/methodology/approachThis paper analyses the process by which Desjardins Group launched the Desjardins Environment Fund as the first investment fund in North America to integrate environmental screening. It uses longitudinal single case analysis and a theoretical framework based on Teece’s three dynamic cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 44 publications
3
68
0
2
Order By: Relevance
“…However, it is worth pointing out Culture. A proper environment for the creation of SI involves a process of co-building and sharing knowledge between all involved (internal and external) (Vezina et al, 2019), a willingness to improve social well-being that is greater than the fear of failure, strong levels of intrapreneurship and less dependence on a leader that only encourages innovation inwards (Berzin and Pitt-Catsouphes, 2015;Biggeri et al, 2017;Martins et al, 2020;Morais-da-Silva et al, 2016;Pasricha and Rao, 2018;Quandt et al, 2017). For example, when analysing the SI process in a large SE, Altuna et al, (2015) found that the ability to shape societal demand into a new product / service involves a decentralized process of product definition by the Finally, according to Dufays (2019), team members seem further motivated to simultaneously embrace both the social and the commercial dimensions needed for implementation of SI when they have both a mutual interest at stake and a general interest (superimposition of the producer/investor role with the beneficiary role).…”
Section: An Integrated Framework Of Social Innovation Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is worth pointing out Culture. A proper environment for the creation of SI involves a process of co-building and sharing knowledge between all involved (internal and external) (Vezina et al, 2019), a willingness to improve social well-being that is greater than the fear of failure, strong levels of intrapreneurship and less dependence on a leader that only encourages innovation inwards (Berzin and Pitt-Catsouphes, 2015;Biggeri et al, 2017;Martins et al, 2020;Morais-da-Silva et al, 2016;Pasricha and Rao, 2018;Quandt et al, 2017). For example, when analysing the SI process in a large SE, Altuna et al, (2015) found that the ability to shape societal demand into a new product / service involves a decentralized process of product definition by the Finally, according to Dufays (2019), team members seem further motivated to simultaneously embrace both the social and the commercial dimensions needed for implementation of SI when they have both a mutual interest at stake and a general interest (superimposition of the producer/investor role with the beneficiary role).…”
Section: An Integrated Framework Of Social Innovation Managementmentioning
confidence: 99%
“…Most of the studies reviewed proposed management practices that facilitate collaborative work. These practices provided multiple platforms for deliberation to create fertile ground for the recognition of a social opportunity(Vezina et al, 2019) and identification of users' latent needs, which are connected to cultural values and are harder to access(Baek et al, 2019). Some of these practices included: a) design thinking helps in supporting, accelerating and democratizing the innovations involving users and other actors in the conception and development of SI(Selloni and Corubolo, 2017); b) focus group contributes to ensure equality in the perception of the social problem and the choice of the solution to be developed(Mulyaningsih et al, 2014); c) agile method aids the division of the process into small cycles (iterations) where the next steps are defined based on current results, lessons learned and new ideas in a cooperative work between users involved and stakeholders (Castro-Spila et al, 2018); d) techniques that enable peripheral vision (Lettice and Parekh, 2010) and larger teams with higher cognitive heterogeneity (more interpretations of courses of action) (Dufays, 2019) to help identify opportunities from unexpected sources; e) risk management helps to identify the optimal level of risk versus type of innovation(Urban and Gaffurini, 2017); and f) SI evaluation considers the impact throughout the entire chain in order to guarantee that the proposed solution does not generate negative externalities ex ante / ex post the SE's actions(Castro-Spila et al, 2018).…”
mentioning
confidence: 99%
“…First, CSI remains a polysemous notion because the definition of social innovation is deemed to lack conceptual clarity. Numerous scholars have developed diverse typologies of social innovation from various disciplines and with distinct approaches [5][6][7][8][9]. For example, integrating the perspectives of business innovation and social awareness, Dawson and Daniel (2010, p. 16) define social innovation as "the process of collective idea generation, selection and implementation by people who participate collaboratively to meet social challenges [16].…”
Section: Corporate Social Innovationmentioning
confidence: 99%
“…Control variables. Referring to previous studies on behavioral outcomes [8,39,[41][42][43][44], gender (male = 0, female = 1), age, tenure and education level (junior high school or lower diplomas = 0, others = 1) were controlled for.…”
Section: Measurementmentioning
confidence: 99%
See 1 more Smart Citation